2003
DOI: 10.1590/s1516-89132003000400013
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the alcohols produced in fermentations with malt contaminated with trichothecenes

Abstract: In order to study the influence of mycotoxins on the production of alcohols, a fermentative process on a laboratorial scale was simulated. Malt was contaminated with deoxynivalenol and T-2 in different ratios (up to 500 ppb), according to a 3 2 factorial design, and the alcohols obtained after the fermentation were determined through gas chromatography. The results showed that trichothecenes influenced the profile of the alcohols produced bySaccharomyces cerevisiae during the fermentative process of malt, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Reinehr and Furlong reported high methanol and fusel oils concentrations depended on the contamination level of the cereal raw material used for ethanol production. The major compounds found in alcoholic beverages are 1‐propanol ( n ‐propyl alcohol), 1‐butanol ( n ‐butyl alcohol), 2‐butanol ( sec ‐butyl alcohol), isobutanol (2‐methyl‐1‐propanol), and isoamyl alcohol (3‐methyl‐1‐butanol).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinehr and Furlong reported high methanol and fusel oils concentrations depended on the contamination level of the cereal raw material used for ethanol production. The major compounds found in alcoholic beverages are 1‐propanol ( n ‐propyl alcohol), 1‐butanol ( n ‐butyl alcohol), 2‐butanol ( sec ‐butyl alcohol), isobutanol (2‐methyl‐1‐propanol), and isoamyl alcohol (3‐methyl‐1‐butanol).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that cereals contamination with deoxynivalenol (DON) by Fusarium graminearum influenced higher contents of fusel oils and methanol in ethanol production . Moreover, the level of contamination influenced the content of methanol and fusel oils in ethanol production from cereals . Higher alcohols are formed under certain fermentation conditions and are generally regarded as important flavor compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of methanol and methyl acetate during the fermentation indicated that Fusarium ‐contaminated wheat was a pure growing medium for yeasts. Studies by Reinehr and Furlong40 demonstrated that unpredictable productions of methanol and higher alcohols could be obtained during the fermentation process of malt, depending on the presence of fungal contamination in cereals. Results of present study and those of Reinehr and Furlong40 suggest that when grains are contaminated with trichothecenes, quality control must be present during fermentation process due to higher concentrations of alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Reinehr and Furlong40 demonstrated that unpredictable productions of methanol and higher alcohols could be obtained during the fermentation process of malt, depending on the presence of fungal contamination in cereals. Results of present study and those of Reinehr and Furlong40 suggest that when grains are contaminated with trichothecenes, quality control must be present during fermentation process due to higher concentrations of alcohols. A decrease in methanol and methyl acetate as well as isoamyl and isobutyl alcohols, obtained after enzymatic hydrolysis of Fusarium ‐contaminated wheat using T. reesei preparation, sustains the advisable use of the xylanolytic complex for wort saccharification.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of methanol and methyl acetate during the fermentation indicated that Fusarium-contaminated wheat was a pure growing medium for yeasts. Studies by Reinehr and Furlong demonstrated that unpredictable productions of methanol and higher alcohols could be obtained during the fermentation process of malt, depending on the presence of fungal contamination in cereals [151]. )…”
Section: Impact Of Enzymes On Alcohol Fermentation Of Mycotoxin Contamentioning
confidence: 99%